Experimental and numerical evaluations of the distribution and effect of roll-forming residual stress on CFS sigma beams. (April 2020) - Wang, Feiliang; Yang, Jian; Azim, Iftikhar; Bai, Li; Ma, Yanling
Abstract: As a high-efficiency and versatile production approach, roll forming process, which involves a continuous roll set system, can bend the flat sheet to targeted sectional configurations gradually. During the process, the sheet experiences a repeat bending-unbending at each roll set and residual stress will hence be induced as it is loaded beyond the elastic limit. To understand the relationship between the issued residual stress and the load-bearing capacity of the sigma beam, this paper reveals the residual stress distribution in cold roll-formed beam with sigma sections by using dynamic numerical analysis at the first instance. Such initial Finite element Analysis (FEA) outcomes were compared and validated by X-ray diffraction measurement results. Good agreement was achieved in terms of stress distribution and magnitude. Using these reliable residual stresses as input, more numerical models of the roll-formed sigma beams with internal support were established to investigate the influences of residual stress on the load-bearing capacity of the beam. The outcomes obtained indicate that the ultimate load-bearing capacity of the sigma beam is slightly decreased in the presence of the residual stress, as the resistance of the innerweb will be deteriorated by the compressive residual stress in the place. Highlights: Numerical simulation for roll forming process of sigma section. Predicted residual stresses were validated by X-ray diffraction test. Good agreement between the model predictions and experimental measurements. The strain hardening during roll forming was estimated by laboratory tests. The effects of residual stress and strain hardening on roll-formed beams were studied.